Effect of cyclosporin A on inflammatory cytokine production by U937 monocyte-like cells - Juan E. Losa Garcia; María Rosa Martín de Cabo; Fernando Mateos Rodríguez; Jesús Pérez Losada; Antonio Jiménez López; José Luis Pérez Arellano (Mediators of Inflammation)
Cyclosporin A (CsA) is an immunosuppresor drug that has been used in the treatment of several types of inflammatory diseases. In some of them the inhibition of T-lymphocyte activation does not suitably account for the observed beneficial effect, suggesting that CsA could act on other types of cells. The present study was undertaken to determine the effect of CsA on inflammatory cytokine secretion by U937 monocyte cells. Undifferentiated and dimethylsulfoxide (DMSO) differentiated U937 cells were incubated with different concentrations of CsA (200, 20 and 2 ng/mL) in the presence or absence of phorbol-myristateacetate (PMA). Interleukin-1g (IL-1β), tumor necrosis factor-α (TNF-α), IL-6 and IL-8 levels were measured in supernatants using specific enzyme-linked immunosorbent assays. At the highest concentration used (200 ng/mL) CsA decreased the basal and stimulated secretion of all the inflammatory cytokines studied in both undifferentiated and differentiated cells, with the only exception of PMA-stim ulated IL-1 secretion by undifferentiated cells. However, only basal secretion of interleukin-8 in both undifferentiated and DMSO-differentiated U937 cells was significantly reduced by CsA at the highest concentration (200 ng/ mL). At therapeutic concentrations in vivo, CsA exerts a predominant effect on IL-8 secretion by human mononuclear phagocytes.